Drone’s objective inference using policy error inverse reinforcement learning - Perrusquía, Adolfo; Guo, Weisi (Institute of Electrical and Electronics Engineers (IEEE), 2025)
Drones are set to penetrate society across transport and smart living sectors. While many are amateur drones that pose no malicious intentions, some may carry deadly capability. It is crucial to infer the drone’s objective to prevent risk and guarantee safety. In this article, a policy error inverse reinforcement learning (PEIRL) algorithm is proposed to uncover the hidden objective of drones from online data trajectories obtained from cooperative sensors. A set of error-based polynomial features are used to approximate both the value and policy functions. This set of features is consistent with current onboard storage memories in flight controllers. The real objective function is inferred using an objective constraint and an integral inverse reinforcement learning (IRL) batch least-squares (LS) rule. The convergence of the proposed method is assessed using Lyapunov recursions. Simulation studies using a quadcopter model are provided to demonstrate the benefits of the proposed approach.
Keywords: Drones; inverse reinforcement learning (IRL); objective function; online trajectories; policy error; weight matrices